PENGARUH BELANJA DAERAH FUNGSI KETERTIBAN DAN KEAMANAN, PENYALURAN BANTUAN SOSIAL DAN TARAF KESEJAHTERAAN MASYARAKAT TERHADAP TINGKAT KRIMINALITAS DI JAWA TIMUR: (PENGARUH BELANJA DAERAH FUNGSI KETERTIBAN DAN KEAMANAN, PENYALURAN BANTUAN SOSIAL DAN TARAF KESEJAHTERAAN MASYARAKAT TERHADAP TINGKAT KRIMINALITAS DI JAWA TIMUR) - Awaliyah Khusyhi, Aini; Rachmawati, Lucky (Jurnal Ekonomika : INDEPENDEN, 2025)
Crime in East Java Province is influenced by security policies, social interventions, and regional economic conditions; therefore, an empirical analysis is required to determine the influence of each factor. This study aims to analyze the effect of regional government expenditure on public order and security, the distribution of social assistance, and the level of community welfare on crime rates in East Java Province during the period 2019–2023. This research employs a quantitative approach using secondary data obtained from the Central Statistics Agency and the Directorate General of Fiscal Balance of the Ministry of Finance. The analytical method used is panel data regression with a Fixed Effect Model (FEM), processed using EViews 13 software. The results show that government expenditure on public order and security has a negative and significant effect on crime rates, while social assistance distribution and the level of community welfare have positive and significant effects. Simultaneously, all three variables have a significant effect on crime rates in East Java Province during 2019–2023.